Nipple adenoma: A report of two cases - Ting-Ting Yang; Yue-Chiu Su; Cheng-Che E Lan (Wolters Kluwer Medknow Publications, 2020)
Nipple adenoma is a rare benign tumor of the nipple due to mammary proliferation of the lactiferous ducts. Common presentation of the tumor includes nipple erosion, erythema, scaling, and eczematous change of the overlying skin. Delayed diagnosis is common since its clinical presentation resembles that of other benign or malignant condition of the nipple, such as nipple eczema or Paget's disease. Timely identification with histopathological correlation is essential for appropriate management. We herein describe the clinical and histopathological characteristics of two cases of nipple adenoma.